Viability of fabricating a microfludic biochip without microfabrication processess - Lim, Jonethan You Xiong. (2013)
Polymerase Chain Reaction (PCR) is a technique that is used for replicating a DNA or RNA strand template. Over the years since its introduction, variants of this technique have emerged. One of these variants is Digital PCR (dPCR). dPCR is refinement of the original PCR technique in that it is more reliable and sensitive in the measurement of nucleic acid amounts.